2009
DOI: 10.2341/08-80
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength of Resin Cements to a Zirconia Ceramic with Different Surface Treatments

Abstract: ©Operative Dentistry, 2009, 34-3, 280-287 AN Cavalcanti • RM Foxton • TF Watson MT Oliveira • M Giannini • GM Marchi Clinical RelevanceAir abrasion and the use of special functional monomers that are able to chemically bond to zirconium dioxide can improve adhesion to a highly dense zirconia ceramic. Fragments of dentin with a cylindrical edge (0.8 mm in diameter) were fixed to ceramic surfaces with the resin cements. The micro-shear bond test was carried out at a 1 mm/minute speed until failure, and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
201
2
27

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(244 citation statements)
references
References 21 publications
14
201
2
27
Order By: Relevance
“…Zirconia demonstrates great potential as a substitute for myriad traditional materials in many dental applications, such as orthodontic brackets, posts, implant abutments, and frameworks for inlays, crowns, and bridges 1) . The mechanical properties of zirconia are the highest ever reported for any dental ceramic, boasting of high flexural strength and toughness [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Zirconia demonstrates great potential as a substitute for myriad traditional materials in many dental applications, such as orthodontic brackets, posts, implant abutments, and frameworks for inlays, crowns, and bridges 1) . The mechanical properties of zirconia are the highest ever reported for any dental ceramic, boasting of high flexural strength and toughness [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…21 Notwithstanding, controversy exists regarding the efficacy any of these treatments. 16,22,23,24 Air blasting with glass beads is another attempt to modify the zirconia surface and increase the bond strength between zirconia-based ceramics and resin cement. Previous studies have indicated that the fusion of glass beads on a zirconia surface can increase the bond strength to composite resin cements, as compared with untreated surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente, existem diversos sistemas à base de zircônia, entre eles os com um conteúdo de dióxido de zircônia maior que 90%, chamadas Y-TZP e as cerâmicas infiltradas por vidro com 35% de zircônia parcialmente estabilizada, podendo ser aplicadas em uma grande variedade de procedimentos, que vão desde pilares protéticos para implantes à infraestruturas unitárias ou de vários elementos 5,24 . Os sistemas Cercon (DeguDent) e Lava All-Ceramic System (3M/ESPE) utilizam esse tipo de cerâmica no qual as restaurações são confeccionadas pelo procedimento de fresagem.…”
Section: Base De Zircôniaunclassified